Solar center-to-limb variation in Rossiter-McLaughlin and exoplanet transmission spectroscopy - Reiners, Ansgar; Yan, F.; Ellwarth, M.; Ludwig, Hans-Günter; Nortmann, L. (Astronomy and astrophysics, 2023)
Line profiles from spatially unresolved stellar observations consist of a superposition of local line profiles that result from observing the stellar atmosphere under specific viewing angles. Line profile variability caused by stellar magnetic activity or planetary transit selectively varies the weight and/or shape of profiles at individual surface positions. The effect is usually modeled with radiative transfer calculations because observations of spatially resolved stellar surfaces are not available. For the Sun, we recently obtained a broadband spectroscopic atlas of the solar center-to-limb variation (CLV). ...
Online veröffentlicht am 5. Mai 2023
Gesehen am 07.12.2023